2001
DOI: 10.1210/jcem.86.9.7866
|View full text |Cite
|
Sign up to set email alerts
|

GH, GH Receptor, GH Secretagogue Receptor, and Ghrelin Expression in Human T Cells, B Cells, and Neutrophils

Abstract: We examined GH and GH receptor expression in human leukemic cell lines and leukocytes of normal subjects to elucidate the cell types expressing GH and GH receptor, the individual variations of their expressions, their correlation and the relationships with serum IgG and IGF-I concentrations. In addition, the expression of GH secretagogue receptor, which enhances GH secretion from the anterior pituitary by synthetic GH secretagogues and that of its endogenous ligand, ghrelin, were also examined in these immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
78
0
15

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(98 citation statements)
references
References 36 publications
5
78
0
15
Order By: Relevance
“…In pituitary-intact rats, treatment with ghrelin reduced the colitis-evoked increase in mucosal concentration of those indices of inflammation. This anti-inflammatory effect of ghrelin could be a result of its direct action on ghrelin receptors present on the membranes of the immune system cells [64,65]. However, experiments performed on hypophysectomized rats indicated that the anti-inflammatory effect of ghrelin in acetic acid-induced colitis is related to the release of endogenous growth hormone and IGF-1.…”
Section: Discussionmentioning
confidence: 99%
“…In pituitary-intact rats, treatment with ghrelin reduced the colitis-evoked increase in mucosal concentration of those indices of inflammation. This anti-inflammatory effect of ghrelin could be a result of its direct action on ghrelin receptors present on the membranes of the immune system cells [64,65]. However, experiments performed on hypophysectomized rats indicated that the anti-inflammatory effect of ghrelin in acetic acid-induced colitis is related to the release of endogenous growth hormone and IGF-1.…”
Section: Discussionmentioning
confidence: 99%
“…Within the subset of T cells, GHR expression is the lowest in cluster of differentiation 4+ T cells. Not only do immune cells express GHR, indicating that they may respond to GH, many immune cells also express GH [127]. In agreement with the pattern of GHR expression, GH gene and protein expression is highest in B cells, although the level of secreted GH was near the detection limit.…”
Section: Effects Of Growth Hormone In the Intestine During Inflammmentioning
confidence: 83%
“…The expression of both GH and GHR by B cells indicates that GH action in these cells may be through an autocrine/paracrine pathway. The authors did not find any correlation between B cell GH/GHR expression and serum Immunoglobulin G or IGF-1, respectively [127]. …”
Section: Effects Of Growth Hormone In the Intestine During Inflammmentioning
confidence: 99%
“…The presence of mRNA signal for GHS-R and/or its production has been demonstrated in an organism both in the central structures [57,69,70] and in the peripheral tissues [24,70,71,72]. Genetic expression of GHS-R type 1a has been identified in the thyroid, pancreas, spleen, cardiac muscle and adrenal gland.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, GHS-R type 1b has been widely detected in the following systems: digestive, respiratory, cardiovascular, endocrine, reproductive, excretory and immune. Moreover, it has also occurred in the skin, breast, buccal mucosa, muscle and fat tissue [24,70,71,72]. …”
Section: Discussionmentioning
confidence: 99%